Pengaruh Tingkat Suku Bunga Sertfikat Bank Indonesia Terhadap Perubahan Nilai Tukar (Kurs) Rupiah Atas Dolar Amerika: Granger Causalitas Test - Ferdinandus Stenly (Universitas Airlangga, 2010)
The Bank of Indonesia Certificate is one of monetary instruments that used by government to influence IDR Exchange Rate Movement Over USD. The purpose this research is to obtain the describe more detailed about influence Certificate Bank of Indonesia toward an IDR Exchange Rate Movement Over USD which try to give an information in a common manner to be concerned outsider espacially relate to government policy. This research using the secondary data with limit that analysis during 20 months that are from November 2005 to June 2007. In compile this thesis, the author carry out the causality relationship analysis (causality) with Granger Causality Test (GCT) and relationship closeness analysis which using Ordinary Least Square (OLS) regresion analysis. The Granger Causality Test (GCT) analysis result explains that from analysis result obtained as model considered valid is the rate interest of SBI has influence toward an IDR Exchange Rate Movement over USD. This was proved on GCT test too much significant for Y = f (x) and not on contary X = f (y). The analysis result of Ordinary Least Square (OLS) was obtained Ftest (2,18) is 266,081 > Ftable 6,01. This means as variable an independent influence variable dependent. Beside that was obtained ttest 16,312 > ttable 2,21009 that mean the rate interest level of SBI has the influence signicant toward an IDR Exchange Rate Movement Over USD. Because the Certificate of Bank of Indonesia has negative influence towards IDR Exchange Rate Movement Over USD, the author suggests the Indonesia Government to defend and to optimalyze the existing instrument, so that the monetary condition is more controlled and the stability can be maintained.